Metro Engineering Project Schedule Optimization Based on Wireless Network Communication and BIM Model Algorithm - Jiang, Haidong; Tian, Manli; Chen, Yonggui; Zhang, Guofa; Peng, Xiaoyong (Scientific programming, 2022)
BIM (Building Information Modeling) is to create models based on various related information in construction projects and use simulation virtual technology to model actual building information. It is not only the integration of digital information but also the application of digital information in engineering construction. Digital models can be used to plan and simulate the whole process of construction projects scientifically and accurately. In the process of project construction, wireless network communication technology can provide a good basis for collaboration, which is essential for the control of project progress, task scheduling, and systematic communication between all parties. This article introduces the LTE wireless network communication technology and network coverage plan, summarizes the cost and schedule control principles of construction projects, analyzes the factors that affect the construction schedule in subway construction, and introduces the application of BIM technology in subway construction schedule control. Taking the construction of Section XX of Line 1 of City A as an example, a simulation experiment was carried out, and the optimization effect was evaluated with SPI and CPI indicators. The final experimental results show that it is meaningful to use the BIM model algorithm to optimize the subway project. In the simulation experiment, the corresponding construction period saving rate after completion of the project is 6.94%.